Le mouton Djallonke de Cote-d'Ivoire en milieu villageois - Comportement et alimentation - Rombaut, D.; Vlaenderen, G. (1976)
Description of the West African Dwarf Sheep, its behaviour and feeding in village environment, particularly animal health, lack of breeding management techniques, nutrient requirement, animal performance and possibilities for its improvement - Data on feed value of tropical forage species.